PHYTOTOXIC EFFECT OF EUGENOL TOWARDS TWO WEEDY SPECIES - R. K. KOHLI; S. VAID; DAIZY R. BATISH; H. P. SINGH (The Bioscan, 2010)
A study was undertaken to assess the inhibitory / allelopathic potential of eugenol–a volatile monoterpene found in Eugenia spp. and several other aromatic plants, against two weedy species viz. Cassia occidentalis and Bidens pilosa. Eugenol significantly inhibited the germination of both the weeds even at very low concentration. However, the effect was more on B. pilosa compared to C. occidentalis. Likewise, the seedling growth measured in terms of seedling length and dry weight of both the test weeds was appreciably reduced in response to the test monoterpene. Not only the growth, even the content of the total chlorophyll and cellular respiration in both the test weeds were appreciably reduced, thereby indicating that eugenol negatively affects the photosynthetic efficiency and the energy metabolism of the weed species. Based on the study, it is concluded that eugenol possesses weed-suppressing ability and can be used for future weed management programmes either directly or by serving as a lead molecule.